METHODS FOR THE DEVELOPMENT OF PROFESSIONAL SKILLS OF COMPUTER SCIENCE TEACHERS IN THE MODERN DIGITAL ENVIRONMENT - Vahobov Adkham Bahodirovich (Web of Journals Publishing, 2025)
The rapid development of information and Communication Technologies is bringing about fundamental changes in the educational system. Especially in the field of teaching informatics, the importance of the digital environment is growing. The modern digital environment allows teachers to use new pedagogical approaches, interactive lessons, online resources, and various innovative tools. Therefore, it is very important to constantly develop the professional skills of Informatics teachers, to deeply introduce them to digital technologies and adapt them to modern requirements.
Keywords: Modern technologies, Informatics, professional skills, knowledge, skills, education, abilities, online platforms